42 | x | ÷ | ( | 21 2 | × | 3 10 | ) | + | 367 10 | = | 149 2 | x |
Multiply both sides of the equation by: | ( | 21 2 | × | 3 10 | ) |
42 | x | + | 367 10 | ( | 21 2 | × | 3 10 | ) | = | 149 2 | x | ( | 21 2 | × | 3 10 | ) |
42 | x | + | 367 10 | × | 21 2 | × | 3 10 | = | 149 2 | x | ( | 21 2 | × | 3 10 | ) |
42 | x | + | 367 10 | × | 21 2 | × | 3 10 | = | 149 2 | x | × | 21 2 | × | 3 10 |
42 | x | + | 23121 200 | = | 9387 40 | x |
42 | x | − | 9387 40 | x | = | - | 23121 200 |
- | 7707 40 | x | = | - | 23121 200 |
23121 200 | = | 7707 40 | x |
7707 40 | x | = | 23121 200 |
x | = | 23121 200 | ÷ | 7707 40 |
= | 23121 200 | × | 40 7707 |
= | 1101 5 | × | 1 367 |
x | = | 1101 1835 |
x | = | 0.6 |